Investigating the Phylogenetic Diversity of SARS-CoV-Like Viruses in Various Species of Bats in Sarawak, Malaysia - Sultana Parvin, Habeebur-Rahman (UNIMAS, 2025)
Bats are natural reservoirs for a diverse range of coronaviruses (CoVs), including those closely related to SARS-CoV and SARS-CoV-2. Their unique ecological traits, including high mobility, diverse dietary habits, and social roosting behavior, facilitate viral maintenance and transmission, making them critical subjects for understanding zoonotic spillover risks. Despite Malaysia's rich bat diversity, particularly in Sarawak, studies on bat CoVs (BtCoVs) remain limited. This study aims to fill this gap by investigating the prevalence, diversity, and phylogenetic relationships of bat CoVs in western and northern Sarawak, Malaysian Borneo. A total of 346 fecal samples were collected from 29 bat species spanning six families, including Pteropodidae, Hipposideridae, Vespertilionidae, Miniopteridae, Nycteridae, and Rhinolophidae. To ensure comprehensive detection, two widely used molecular assays, the Quan (Q-assay) and Watanabe (W-assay) pan-CoV PCR protocols, were employed. The selection of these assays was based on their established sensitivity in detecting both known and potentially novel CoV lineages by targeting conserved regions of the RNA-dependent RNA polymerase (RdRp) gene. The Q-assay has been widely utilized for detecting a broad range of CoVs across various host species, while the W-assay is optimized for bat-associated CoVs, making their combined application suitable for evaluating detection efficacy. The performance of both assays was statistically compared using the Kappa statistic and McNemar’s test to assess agreement and detection differences. The results revealed a CoV prevalence of 14.45% with the Q-assay and 12.72% with the W-assay, with a combined prevalence of 22.83%. The two assays demonstrated fair agreement (κ=0.286, p<0.001) and no statistically significant difference in detection capability (McNemar’s p>0.05), indicating comparable performance in identifying bat CoVs. Phylogenetic analysis of RdRp sequences identified six distinct clades within alphacoronaviruses (α-CoVs) and betacoronaviruses (β-CoVs), including two unclassified Borneo-α-CoVs and four classified CoVs within the subgenera Minunacovirus, Rhinacovirus, Nobecovirus, and Sarbecovirus. Notably, Sarbecovirus-related sequences were detected in Rhinolophidae bats, further supporting their role as key reservoirs of viruses related to SARS-CoV and SARS-CoV-2. The use of two molecular assays provided a more comprehensive picture of CoV diversity and demonstrated the importance of using complementary detection methods. While both assays showed similar detection capabilities, their combined use allowed for the identification of a broader range of CoVs, including potentially novel strains. This study represents the first detailed phylogenetic analysis of bat CoVs in Sarawak derived from fecal samples, addressing a significant research gap. The findings underscore the importance of continued surveillance efforts in high-biodiversity regions to improve understanding of CoV ecology and mitigate zoonotic risks. Future research should explore whole-genome sequencing approaches to further characterize unclassified CoV clades and refine molecular assays for enhanced detection.